'Everything is there, but they don't bring it to your front door … ' An analysis of the perception of early childcare by parents of children with disabilities. Issue 1 (2nd January 2023) - De Schauwer, Elisabeth; Vandenbussche, Hanne; Van Hove, Geert
ABSTRACT: In Flanders, we are searching to implement inclusion in our educational systems, knowing that we have a strong focus on segregation and specialisation. Parents are often missing in the debate, while they are confronted with experiences of exclusion and discrimination. Our aim was to hear the parents' voices on high-quality childcare for children with disabilities between 0 and 3 years old. As part of the evaluation of inclusive childcare practices by the Flemish government, we undertook interviews with 20 parents of children with disabilities (0–6 years). Some families are still in the early childcare centre and others are looking back, while already in preschool. We elaborated on what support parents find valuable and how this can be embedded in inclusive early childcare. We came to four themes: deciding on the childcare type parents prefer, negotiating power with professionals, exploring lived experiences in early child care and finally the evaluation of inclusion by parents in early care. We keep coming back to the importance of listening in involving parents of very young children with disabilities.